Has China displaced the outward investments of OECD countries? - Yao, Shujie; Wang, Pan (Elsevier, 2014)
As China has rapidly emerged as one of the world's largest investors abroad, there has been a hectic debate in the literature on whether its emergence as a major foreign investor may have undermined the importance of western industrialised economies, including those in the Organisation for Economic Cooperation and Development (OECD). This paper aims to investigate whether this is the case. The study uses a panel dataset covering 155 countries, including 33 in the OECD, where China had invested during 2003–09. This is by far the most comprehensive dataset of China's outward foreign direct investment (OFDI). A two-stage least squared (TSLS) regression approach is adopted for our econometric models according to an established augmented gravity model in the literature. The empirical results show clear evidence that China's OFDI displaces that of the OECD countries, but the argument that China's emergence is a ‘new colonialism’ is not supported as OECD countries' OFDI in resource abundant host countries, particularly that in Africa and Latin America, does not appear to have been displaced by China's OFDI.